STUTTERING PATTERNS IN ADULT PUBLIC SPEECH: A PSYCHOLINGUISTIC ANALYSIS OF SHARON’S TEDX TALKS - Yayu Anggraini H. Katili; Usman Pakaya (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to analyze the types of stuttering speech disorders in an English speaker. The data source of this study is a YouTube video titled “The Power of a Stutter” by Sharon Steed, a person who experiences stuttering, published on the TEDx Talks  channel. This research employed a qualitative descriptive method using listening and note-taking techniques to identify instances of stuttering in the speaker’s presentation. The results show that 124 instances of stuttering occurred within the 17 minutes and 33 seconds duration of the video. The analysis reveals that prolongation was the most dominant type of stuttering, occurring 40 times (32.3%). Repetition occurred 34 times (27.4%), while blocking occurred 33 times (26.6%). Mixed patterns were identified 17 times (13.7%). These findings indicate a relatively balanced distribution among the three primary types of stuttering observed in the speaker’s speech. This suggests that the stuttering disorder experienced by the speaker is complex and involves multiple forms of disfluency rather than a single dominant type, which is commonly associated with persistent stuttering in adults.